Effects of Bone Marrow Mesenchymal Stem Cells in Damaged Knee Articular Cartilage of Wistar Albino Rats- A Histopathological and Radiological Anatomy Study. - Dr Nirmal Kumar K; Dr Kalyana Panchakshari P; Dr Srikanth K (International Journal of Pharma and Bio Sciences, 2023)
Knee osteoarthritis (OA) is a joint disease that can limit mobility and affect an individual's life quality. As empirical evidence significantly reported that there is no complete cure for OA knee in human beings, this study aimed to find the effectiveness of Bone marrow mesenchymal stem cells (BMMSCs) in treating the damaged articular cartilage of knee joint in Wistar albino rats. 15 male Wistar albino rats were divided into 3 groups. Control group (n=4 rats)- Normal rats, Experimental Group A (n=5 rats)- Rats with damaged articular cartilage deprived of BMMSCs treatment, and Experimental Group B (n= 5 rats)- Rats with damaged articular cartilage treated with BMMSCs. Trauma mimicking OA was created in the left knee joint of experimental rats. One rat was used for BMMSCs culture. Cultured BMMSCs were transplanted into the left knee joint of group B rats. On the 7th, 14th, and 28th day, histopathological and radiological analysis of articular cartilage was performed in all group rats. Hematoxylin and Eosin (H and E) stains were used for histopathological investigation, and a Modified Mankin score was used to grade it. Administration of BMMSCs drastically reduced knee swelling and ameliorated the alterations in articular cartilage in group B rats histopathologically and radiologically compared to group A rats. This may be due to the paracrine and chondroprotective effects of BMMSCs. BMMSCs could be considered a recovery treatment for OA knee in Wistar albino rats. However, this study achieved its aim not in humans. So, this work advises researchers to examine BMMSCs' effects in healing damaged articular cartilage in higher animal models before moving on to humans.